Problems of east-west interaction in the context of the historical development of Egypt and the politics of european countries (first half of the 19th century) - Zhuldyz, Turekulova; Madiyar, Zhumabekov; Elmira, Taukebaeva (Bulletin of the Karaganda university History.Philosophy series, 2024)
This article examines the main directions of the policies of European countries in Egypt in the context of its historical development in the first half of the 19th century. Modern political processes taking place in the Middle East were mainly formed during the era of colonialism, therefore, the study of the policies of European powers, including France and Great Britain policy in Arab countries in the 19th century is of particular importance in understanding the historical background of political conflicts in the Middle East region. The issues caused by the colonial policies of European countries in Egypt have been the subject of a wide array of studies from historical, economic and political perspectives. In scientific works devoted to this topic, the interests of France and Great Britain in Egypt are considered primarily as a part of political-economic or political-strategic direction. At the same time, research in the context of mutual influences between the West and the East, within the framework of colonial modernization and orientalism is a controversial and multifaceted area that requires careful study. In this connection, the article analyzes the main reasons and directions of the policies of France and Great Britain in Egypt. The article considers various colonial policy instruments along with propaganda in scientific and political circles, used by European countries, and by virtue of which the respective political and ideological processes were formed. The main reasons of Great Britain occupation of Egypt are revealed in this article. New methodological approaches are applied in order to scrutinise the correlation of colonial policy and modernisation processes in the East.